A reconceptualized model of self-control and crime: specifying the role of self-control variability - Pratt, Travis C. (Criminal justice and behavior, 2015)
In this article an argument is developed that criminologists? focus on individuals? levels of self-control has caused us to miss another key component within this theoretical tradition: within-individual situational variability in self-control. Accordingly, in the present study, self-control variability is treated as an important theoretical construct that should explain criminal behavior independent of one?s level of self-control. This proposition is tested empirically on a sample of young adults, using measures of both self-control and situational self-control variability in a series of multivariate regression models. The results demonstrate that both self-control and self-control variability exert significant and independent effects on criminal behavior. These results reveal support for a reconceptualized model of self-control that incorporates both static and dynamic dimensions.